Perlindungan Data Pribadi dalam Marketplace Foto Berbasis Kecerdasan Buatan pada Platform FotoYu - Nada Ulya Qinvi; Ridho Sa'dillah Ahmad; Hasmia Wahyunisa (Jurnal Hukum Siber dan Regulasi Teknologi, 2026)
This study examines personal data protection in the practice of an artificial intelligence–based photo marketplace on the FotoYu platform, which utilizes facial recognition technology for photo processing and commercialization. The research focuses on the extent to which the processing of facial biometric data by the photo marketplace platform provides adequate legal protection for data subjects in accordance with the Personal Data Protection Law. The study adopts a normative juridical method, employing a statutory approach and a conceptual approach through the analysis of legal norms, principles, and doctrines of personal data protection. The findings indicate that personal data processing in AI-based photo marketplaces has not fully complied with the principles of explicit consent, purpose limitation, transparency, and the fulfillment of data subject rights. Indirect consent mechanisms and the complexity of AI-driven processing may create a gap between legal norms and practical implementation. The study concludes that personal data protection in photo marketplace practices still requires strengthening, both in terms of regulation and implementation. Therefore, more specific implementing regulations and enhanced platform responsibility and accountability are necessary to ensure effective protection of data subject rights in the digital economy era.